HYPERTENSION EXERCISE AND BLOOD PRESSURE REDUCTION AMONG PATIENTS WITH HYPERTENSION: SENAM HIPERTENSI DAN PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Rosa Zahrotul Firdausa; Joko Suwito; Hilmi Yumni; Anita Joeliantina (Politeknik Kesehatan Kemenkes RI Jakarta I, 2026)
Hypertension is a chronic condition that increases the risk of cardiovascular morbidity and mortality. In addition to pharmacological treatment, non-pharmacological interventions such as hypertension exercise are important components of comprehensive hypertension management. This study aimed to analyze the effect of hypertension exercise on blood pressure reduction among individuals with hypertension. A pre-experimental one-group pretest–posttest design was employed involving 41 participants selected through random sampling. The intervention consisted of eight hypertension exercise sessions conducted over four weeks. Blood pressure was measured before and after the intervention and analyzed using the Paired t-test with a significance level of 0.05. The results showed that mean systolic blood pressure decreased from 141.56 mmHg to 131.24 mmHg, while mean diastolic blood pressure decreased from 83.37 mmHg to 82.51 mmHg. Statistical analysis revealed a significant reduction in systolic blood pressure (p < 0.05), whereas the reduction in diastolic blood pressure was not statistically significant (p > 0.05). It can be concluded that hypertension exercise is effective in reducing blood pressure, particularly systolic blood pressure, but has not shown a significant effect on diastolic blood pressure.